2017
DOI: 10.1155/2017/1479136
|View full text |Cite
|
Sign up to set email alerts
|

Tangzhiqing Granules Alleviate Podocyte Epithelial‐Mesenchymal Transition in Kidney of Diabetic Rats

Abstract: This study discussed the effect of Tangzhiqing granules on podocyte epithelial-mesenchymal transition in kidney of diabetic rats. The diabetic rats were divided randomly into five groups: DM group treated with vehicle, Tangzhiqing granules low-dose treatment group, Tangzhiqing granules middle-dose treatment group, and Tangzhiqing granules high-dose treatment group. Eight Wistar rats used as control group were given saline solution. The intervention was all intragastric administration for 8 weeks. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Moreover, in our study, the diabetic group showed severe desmin immunoreaction that indicate the podocytes injury and this was in accordance with [30] who found a significant increase in desmin protein in the kidneys of diabetic rats and referred these changes to the podocyte injury. The renal tubules demonstrated dilated congested blood vessels, vacuolations, desquamation, degenerated mitochondria, pyknotic nuclei, and wide intercellular spaces.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in our study, the diabetic group showed severe desmin immunoreaction that indicate the podocytes injury and this was in accordance with [30] who found a significant increase in desmin protein in the kidneys of diabetic rats and referred these changes to the podocyte injury. The renal tubules demonstrated dilated congested blood vessels, vacuolations, desquamation, degenerated mitochondria, pyknotic nuclei, and wide intercellular spaces.…”
Section: Discussionsupporting
confidence: 91%
“…EMT of podocytes could be activated in diabetic conditions 15 , 16 and resulted in glomerular fibrosis in ESRD 2 . Previous studies have demonstrated that TGFβ pathway and NFκB pathway played an important role in EMT of podocyte in diabetes mellitus 16 , 17 . However, it is still controversial about how to deal with EMT of podocyte by inhibiting these signaling pathways 18 .…”
Section: Discussionmentioning
confidence: 95%
“…It also increased the susceptibility of glomerular injury, leading to glomerular sclerosis. Defects in CD2AP caused fusion of the foot processes through deposition of the mesangial matrix, resulting in proteinuria [ 53 56 ].…”
Section: Discussionmentioning
confidence: 99%